Relationship of Midwife Knowledge in Management Referral to Maternity and Obstetric Disorders at the Panombeian Panei Health Center, Simalungun Regency in 2022 - Meyana Marbun; Sri Rahma Friani; Eka Saudur Renaldi Sihombing (Institute of Computer Science (IOCS), 2022)
Based on WHO research worldwide, there are 500,000 maternal deaths per year and infant mortality, especially neonates, at 10,000,000 people per year. These maternal and infant deaths occur mainly in developing countries by 99%. Although the number is very large, it does not attract attention because the incidence is widespread, in contrast to deaths that occur due to floods, landslides, other natural disasters or accident victims (Manuaba, 1998). In Indonesia, based on calculations by BPS, the MMR in 2007 was 248/100,000 KH. When compared with the AKI in 2002 of 307/100,000 KH, the MMR has decreased considerably, but is still far from the 2015 MDG (Millennium Development God's) target (102/100,000 KH) so it still requires hard work from all components to achieve the target. But, If we look at the MMR based on the data sent by Puskesmas throughout Indonesia, the MDG's target will be a little more likely to be achieved. Based on reports from all Puskesmas in Indonesia in 2005, the MMR was 151, in 2006 it was 127 and in 2007 it was 119/100,000 KH. This study aims to determine the relationship between the knowledge of midwives in the management of referrals and obstetric disorders at the Panombeian Panei Public Health Center, Simalungun Regency in 2022. This study was a descriptive analytic study with a cross sectional approach. The population in this study amounted to 30 people, and the entire population was used as a sample (total sampling). Respondents' knowledge data were collected using a questionnaire and analyzed using the chi-square test. The results showed that the respondents' knowledge about the management of referrals and obstetric disorders was mostly sufficient for 19 respondents (63.3 %). The chi-squer test on respondents' knowledge with referral management showed p value = 0.001 (p <0.05). From these results it can be concluded that there is a relationship between respondents' knowledge and the management of referrals and obstetric disorders at the Puskesmas. An increase in the knowledge of midwives is needed to increase the decrease in the management of referrals and obstetric disorders.